Analysis of Land Use Change in Langsa City, Aceh Province in 2013 – 2021 - Urfan, Faiz; Sihotang, Zidan; Arrasyid, Riko (Universitas Pendidikan Indonesia, 2022)
Langsa City is a city on the east coast of Aceh that has the fastest growth compared to the surrounding area. However, this has a significant impact on land conversion which reduces environmental quality. Analysis of changes in land use in Langsa City needs to be carried out as a basis for determining development policies. This study aims to analyze changes in land use in Langsa City from 2013 – 2021. The data used in this study are Landsat 8 OLI-TIRS imagery in 2013, 2017, and 2021. These images were analyzed using a supervised classification technique based on band combinations for each land use. The classified land uses are settlements, paddy fields, ponds, mangrove forests, and mixed vegetation. The results showed that there was a significant increase in the settlement area in the center of Langsa City. Meanwhile, other land uses have changed but not consistently. This study concludes that a significant increase in settlement area is due to rapid population growth. The increase in settlement area also has an impact on changes in other types of land use. The researcher recommends that a population growth study be carried out as a basis for determining regional spatial planning.